Self-Assessment System Effect on Revenue Optimization Pph Pasal 25 Corporate Taxpayer At The Sumedang Primary Tax Service Office - Rosi Imelya; Nining Kurniasih; Tiana Feny Krisdina (LPPM Universitas Sebelas April, 2022)
Self-assessment system is a form of government action to get tax revenue to be more optimal. The implementation of the self-assessment system requires the active role of the taxpayer, by voluntarily the taxpayer must register, calculate, pay and report his own tax payable to the KPP. However, it still has not met the tax revenue target. Purpose of this study was to determine how the effect of the self-assessment system on the optimization of income tax revenue PPh Pasal 25 corporate taxpayers at the Sumedang Pratama Tax Service Office. This research method uses quantitative descriptive with a survey approach. The sampling technique used simple random sampling method. The population of this research is corporate taxpayers registered at KPP Pratama Sumedang as many as 100 respondents. The data in this study were obtained primary (questionnaire). The analysis technique used is correlation coefficient analysis, simple regression analysis, coefficient of determination analysis, and hypothesis testing. The results showed that the implementation of the self-assessment system had a positive and significant effect on optimizing income tax revenue PPh Pasal 25. This was shown by the regression equation Y = 8.574 + 0.814X, and 9.429 tcount value > 1.984 t table with a value of sig. 0.000 < 0.05 probability value. With a coefficient of determination of 47.6% and the remaining 52.4% is influenced by other factors.